Agronomic biofortification: Uncovering the evidence. A seminar organized by the Excellence in Agronomy Agronomic Initiative - Maguta, Job Kihara; Gudeta, W Sileshi; Bolo, Peter Omondi; Mutambu, Dominic Mwanzia; Sila, Andrew Musili (2023)
Human Zn and Fe deficiencies can be reduced through agronomic biofortification, but information on factors influencing maize grain-Zn and -Fe levels remains scant.